Gaussian beam diffraction in free space - Berczyński, Paweł; Kravtsov, Yury (Photonics Letters of Poland, 2013)
In this paper complex geometrical optics (CGO) method is applied for Gaussian beam (GB) diffraction in free space. CGO reduces diffraction description to solving ordinary differential equations for the beam amplitude and for complex curvature of the wave front. We present analytical solutions for GB width, wave front curvature and complex amplitude. Moreover we discuss the influence of beam ellipticity on propagation in free space. Obtained CGO solutions are compared with solutions of diffraction theory, specifically from Kirchhoff-Fresnel integral. Full Text: PDF References Yu. A. Kravtsov, "Complex rays and complex caustics", Radiophys. Quantum Electronics 10, 719−730 (1967). CrossRef J. B. Keller and W. Streifer, "Complex rays with application to Gaussian beams", J. Opt. Soc. Am. 61, 40−43 (1971) CrossRef G. A. Deschamps, "Gaussian beam as a bundle of complex rays", Electron. Lett. 7(23), 684−685 (1971). CrossRef Yu. A. Kravtsov, G.W. Forbes, and A.A. Asatryan, "Theory and applications of complex rays", in Progress in Optics, edited by E.Wolf, 39, 1−62 (Elsevier, Amsterdam, 1999). CrossRef S. J. Chapman, J.M. Lawry, J.R. Ockendon, and R.H. Tew, "On the theory of complex rays", SIAM Review 41, 417−509 (1999). CrossRef Yu. A. Kravtsov, P. Berczynski, "Gaussian beams in inhomogeneous media: a review", Stud. Geophys. Geod. 51(1), 1-36 (2007). CrossRef Yu A. Kravtsov N. Y. Zhu, "Theory of diffraction: Heuristic Approaches", Alpha Science International, ISBN 1842653725, (2009). P. Berczynski, Yu.A. Kravtsov, "Theory for Gaussian beam diffraction in 2D inhomogeneous medium, based on the eikonal form of complex geometrical optics", Physics Letters A, 331(3-4), 265-268, (2004). CrossRef P. Berczynski, K. Yu. Bliokh, Yu. A. Kravtsov, A. Stateczny, "Diffraction of Gaussian beam in 3D smoothly inhomogeneous media: eikonal-based complex geometrical optics approach", J. Opt. Soc. Am. A, 23(6), 1442- 1451 (2006). CrossRef P. Berczyński, Yu. Kravtsov, "Gaussian beam evolution in nonlinear inhomogeneous fibres", Photonics Letters of Poland, Vol 4, No 1, 26-28 (2012). CrossRef P. Berczynski, Yu. A. Kravtsov, G. Zeglinski, "Gaussian beam diffraction in inhomogeneous media of cylindrical symmetry", Optica Applicata (Vol.40), No.3, pp. 705-718, (2010). DirectLink